INSPIRASI ALGORITMA SEMUT DALAM ALQUR’AN - M.A. Hariyadi (lp2m-uin malang, 2007)
Ant is conspecific of creation insect of having prayer beads diligent God to God. If we check and studies behavior of ant hence would ever greater of our love to God as well as we would increasingly pays attention to fellow being which his(its must be each other remind and looks after, tries seeing behavior of ant that is in harmony and has soul a friend at court a real height. Subhanallah! Ant animal haves the power of remarkable in realizing its(the intention to reach for what wanted, s(he have never owned go against the stomach and hopeless. So ant is animal taken as example of peer in the case of strong ambition and intention doing not know hopeless word. Ant has a real extraordinary ability in wading river that is by the way of wading river and swims, though not a few of they submerged brought river current, but with all energy?powers and effort they make every effort wades river. From behavior of ant we can build prototyping Ant Algorithms. Ant Algorithms basically is a colony from artificial Ant and designed to solve problem certain. Ant algorithm is a class heuristik which based on at seeking algorithm applied to break many problemses of combinatorial optimization. It is really this became Iesson to us that very extraordinary ant of soul helps each other it. As Islam believer, we try to imitate behavior of ant. We are Islam believer is you which ought to be each other help each other not instead is each other hurt and often happened quarrel though only difference way of approach only. Coalesces wahai Islam believer in the world.Keyword : Ant Algorithms, combinatorial